Pengaruh Pembelajaran Contextual Teaching And Learning Terhadap Hasil Belajar Siswa Kelas IV Pada Mata Pelajaran Akidah Akhlak : Pembelajaran CTL - Siti Nurhayati; Nana Mulyana; Supriyatin (Edusifa: Jurnal Pendidikan Islam, 2023)
ABSTRACK Contextual Teaching and Learning is a learning process that links the material being studied with students' real life or student experiences. With the development of science, students' ways of thinking also develop which need to be directed by a learning process that is able to provide students with an understanding of the material being studied. The understanding that will be obtained based on the experience or real life of students will be easier to remember. This study aims to determine the effect of Contextual Teaching and Learning of fourth grade students’ learning outcomes on the subject of moral aqidah at SDIT Baitul Hilmi Cibinong. The method used in this study is a quantitative method. This method is used to determine the extent of the influence of contextual teaching and learning on the learning outcomes of fourth grade students on the subjects of aqidah morality at SDIT Baitul Hilmi Cibinong. The research instrument used to obtain data was by using a questionnaire (questionnaire) in the form of a checklist. Data processing is carried out by correlation analysis of Product Moment. The variables studied in this study are the influence of contextual teaching and learning (X) on learning outcomes of morals (Y) Based on the product moment analysis, the value of "r" count = 0.499. By examining the table for the value of 'r" product moment, it turns out that for dk = N-2 = 28-2 = 26 at a significant level of 5%, we get "r" table = 0.388 and at a significant level of 1%, we get an "r" table of 0.496. Then it can be concluded that "r" count = 0.499> "r" table. So that Ho is rejected, and Ha is accepted, meaning that there is a positive correlation between contextual teaching and learning and the learning outcomes of moral aqidah. Also mind to the "r" count = 0.499 in the interpretation of the data between 0.40-0.599 this number shows that between the X variable and Y variable there is indeed a "Strong Enough" correlation. The learning contribution of contextual teaching and learning has a significant effect, the number reaches 24.90% and the remaining 75.1% is influenced by other factors not examined. Contextual , Teaching, Learning